2018
DOI: 10.4103/abr.abr_85_18
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Propofol and Ketamine Combination (Ketofol) and Propofol and Fentanyl Combination (Fenofol) on Quality of Sedation and Analgesia in the Lumpectomy: A Randomized Clinical Trial

Abstract: Background:Breast lumpectomy is an integral part of the treatment of mammary masses in women. This study was conducted to evaluate and compare two-drug combinations of propofol–ketamine (PK) (ketofol) and propofol–fentanyl (PF) (fenofol) on quality of sedation and analgesia in lumpectomy.Materials and Methods:This was a randomized, double-blind, clinical trial performed on 64 patients aged 15–70 years with breast cancer lumpectomy referred to Isfahan's Seyed Al-Shohada Hospital. Consequently, patients were div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
1
3
2
1
Order By: Relevance
“…Sedation, analgesia and hemodynamic changes were reported better in Ketofol group. 15 In our study, dose of Fentanyl and Propofol in drug combination were different from the above study but we also found less sedative effect with Fenofol. Haemodynamic effects were comparable between Ketofol and Fenofol.…”
Section: I)contrasting
confidence: 84%
“…Sedation, analgesia and hemodynamic changes were reported better in Ketofol group. 15 In our study, dose of Fentanyl and Propofol in drug combination were different from the above study but we also found less sedative effect with Fenofol. Haemodynamic effects were comparable between Ketofol and Fenofol.…”
Section: I)contrasting
confidence: 84%
“…Sedation, analgesia and hemodynamic changes were reported better in Ketofol group. 18 In our study, dose of Fentanyl and Propofol in drug combination were different from the above study. Haemodynamic effects were comparable between Fentanyl and Fenofol.…”
Section: Discussioncontrasting
confidence: 56%
“…Psychomimetic adverse effects are known to be reduced by concomitant use of propofol [2]. Indeed, the combination has been shown to be useful in many clinical situations, with better profiles in hemodynamic stability, respiratory depression, analgesia, and recovery than each agent alone [2,5,6,7,8,9,10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%